Effect of culture conditions at lab‐scale on metabolite composition and antibacterial and antibiofilm activities of Dunaliella tertiolecta. Issue 2 (9th March 2023) - Iglesias, María José; Soengas, Raquel; López‐Ortiz, Fernando; Biondi, Natascia; Tredici, Mario R.; Gutiérrez‐del‐Río, Ignacio; López‐Ibáñez, Sara; Villar, Claudio J.; Lombó, Felipe; López, Yuly; Gabasa, Yaiza; Soto, Sara
Abstract: Dunaliella tertiolecta RCC6 was cultivated indoors in glass bubble column photobioreactors operated under batch and semi‐continuous regimens and using two different conditions of light and temperature. Biomass was harvested by centrifugation, frozen, and then lyophilized. The soluble material was obtained by sequential extraction of the lyophilized biomass with solvents with a gradient of polarity (hexane, ethyl acetate, and methanol) and its metabolic composition was investigated through nuclear magnetic resonance (NMR) spectroscopy. The effect of light on chlorophyll biosynthesis was clearly shown through the relative intensities of the 1 H NMR signals due to pheophytins. The highest signal intensity was observed for the biomasses obtained at lower light intensity, resulting in a lower light availability per cell. Under high temperature and light conditions, the 1 H NMR spectra of the hexane extracts showed an incipient accumulation of triacylglycerols. In these conditions and under semi‐continuous regimen, an enhancement of β‐carotene and sterols production was observed. The antibacterial and antibiofilm activities of the extracts were also tested. Antibacterial activity was not detected, regardless of culture conditions. In contrast, the minimal biofilm inhibitory concentrations (MBICs) against Escherichia coli for the hexane extract obtained under semi‐continuous regimen using high temperature and irradiance conditions was promising.